M-learning and webquests : the new technologies as pedagogical resource - Bottentuit Junior, João Batista (2006)
This paper has as main goal bring to discussion new educative ways of using information and communication technologies, specifically the use of m-learning to access a webquest. We developed a webquest entitled “Learning with Plants” and it should be used in the Sciences classes in the 5th grade. The mobile devices allow students to access the webquest from the real world, joining theory to practice. Therefore, we believe in the advantages of using these mobile technologies in education. (Portuguese abstract) Esta comunicação pretende trazer para a discussão novas formas de utilização educativa das tecnologias da informação e comunicação, neste caso o uso das tecnologias de m-learning para acesso a uma webquest. A webquest que desenvolvemos chama-se “Aprendendo com as Plantas” e a sua utilização deverá ser feita na disciplina de Ciências da Natureza do 5º ano de escolaridade. Os dispositivos móveis permitem o acesso dos alunos à webquest a partir do mundo real aliando-se assim a teoria com a prática. Defendemos desta forma uma das muitas possíveis vantagens da utilização de tecnologias móveis para fins educativos.